Impact of Tutoring Method on Improving the Quality of Clinical Supervision in the Context of Nursing Education - Abdelilah, Merabti; Abdelrhani, Elachqar; Tarik, Squalli Houssaini; Fatiha, Kaddari (European Scientific Journal, ESJ, 2019)
This paper focuses on the impact of tutoring as a preferred method for clinical supervision of nursing students. The study was conducted by relying upon two main actors of this method, namely: the tutor and the tutored. The development of this work was based on comprehensive and analyticalreadings of previous work to highlight the effects of the tutoring method on the quality of clinical supervision of students. This work allowed us to appreciate the positive side of the impact of this method. Moreover, the analysis made at the end of this work and the figures obtained have allowed us to conclude that a start of tutoring will have significant benefits, mainly, for the tutor: teaching experiences, motivation, and development of critical thinking. Also for the tutored, it includes: the success of the training, the relational support, the construction of the professional identity, and the valorization.